Pengaruh Penambahan Pupuk Bintil Akar Kacang Tanah Sebagai Sumber Nitrogen Dan Fosfor Terhadap Populasi Chlorella sp. [The Effect Of Addition Fertilizer Roots Nodule Peanut As A Source Of Nitrogen And Phosphorus To The Population Of Chlorella sp. ] - Rr. Juni Triastuti; A. Shofy Mubarak; Likanimasayu Prabandari (Jurnal Ilmiah Perikanan dan Kelautan, 2011)
Abstract Chlorella sp. is one natural food that widely used in hatchery fish, shrimp and oyster. The availability of natural food is a factor that has an important role in farming activities. Culture of Chlorella sp. generally use technical fertilizer (Walne) where nitrogen and phosporus in Walne beginning chemist fertilizer the price expensive. One source of nitrogen and phosphorus naturally obtained from the roots of peanuts. The root nodules contained peanut-containing nodule bacteria Rhizobium are able to bind nitrogen from the air element. By doing immersion can be obtained nutrients to the roots of peanuts are nitrogen and phosphorus that is soluble in water. So that the root nodules of peanuts can be used as a source of nitrogen and phosphorus to increase the population of Chlorella sp. The purpose of this study was to determine the effect of the addition of fertilizer and the concentration of peanut root nodules as a source of nitrogen and phosphorus to the population of Chlorella sp. The research was conducted in June until July in the Laboratory of Education Faculty of Fisheries and Marine Fisheries, Airlangga University, Surabaya. The study design used was Completely Randomized Design (CRD). Materials tested in this study was Chlorella sp. whereas fertilizer used is the root nodules of peanut fertilizer and manure Walne. The concentration of the addition of fertilizer peanut nodule is the treatment A (2.25 ppm), treatment B (4.5 ppm), treatment C (9 ppm) and treatment D (18 ppm). Control treatments using fertilizer Walne 0.5 ml/l (control 1) and 1 ml/l (control 2). The main parameter is observed population density, while supporters of the observed parameter is the measurement of temperature, pH and salinity. The results showed that the addition of fertilizer peanut nodule as a source nitrogen and phosporus influence population of Chlorella sp. The addition of fertilizer best peanut nodule is the treatment B of 1,43755x106 cells/ml on the third day. Water quality parameters during the study remained within the tolerance limit for the growth of Chlorella sp. is pH 7-8, room temperature 29-32 0C range, salinity range between 28-40 ppt and water temperature ranges between 28-30 0C.